2020
DOI: 10.3390/molecules26010019
|View full text |Cite
|
Sign up to set email alerts
|

Photo-Isomerization Kinetics of Azobenzene Containing Surfactant Conjugated with Polyelectrolyte

Abstract: Ionic complexation of azobenzene-containing surfactants with any type of oppositely charged soft objects allows for making them photo-responsive in terms of their size, shape and surface energy. Investigation of the photo-isomerization kinetic and isomer composition at a photo-stationary state of the photo-sensitive surfactant conjugated with charged objects is a necessary prerequisite for understanding the structural response of photo-sensitive complexes. Here, we report on photo-isomerization kinetics of a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 35 publications
(48 reference statements)
0
14
0
Order By: Relevance
“…We clearly see that for lower intensities (the isomerization-limited region), we have a constant value for the rate of surfactant isomerization. This value is lower than that for the case of bulk ( k = 0.9 × 10 –2 cm 2 (mW s) −1 in blue and 10 –4 cm 2 (mW s) −1 in green light) and can be explained by the formation of the surfactant aggregates within the gel hindering photoisomerization, as in the case of complexes with linear PAA chains …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We clearly see that for lower intensities (the isomerization-limited region), we have a constant value for the rate of surfactant isomerization. This value is lower than that for the case of bulk ( k = 0.9 × 10 –2 cm 2 (mW s) −1 in blue and 10 –4 cm 2 (mW s) −1 in green light) and can be explained by the formation of the surfactant aggregates within the gel hindering photoisomerization, as in the case of complexes with linear PAA chains …”
Section: Resultsmentioning
confidence: 99%
“…This value is lower than that for the case of bulk (k = 0.9 × 10 −2 cm 2 (mW s) −1 in blue and 10 −4 cm 2 (mW s) −1 in green light) and can be explained by the formation of the surfactant aggregates within the gel hindering photoisomerization, as in the case of complexes with linear PAA chains. 37 To investigate the dynamic exchange of isomer under light exposure as a function of temperature, we irradiate the microgels with blue light (455 nm, I = 2 mW cm −2 ) at different temperatures in the range between 25 and 51 °C (Figure 7a). The rate constant of photoisomerization (calculated using date from Figure 7b and eq 7) of the surfactant as a function of temperature exhibits two regimes before and after ∼32 °C (Figure 7c).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…It can be supplied by a multitude of easily available light-sources, can be targeted to specific spots and remote-operated with adjustability of wavelength and intensity as additional control parameters. 19,20 Crosslinks play a significant role for controlling the microgel properties, especially their softness. 21,22 So far, mainly covalent crosslinks such as N,N-methylenebis(acrylamide) (BIS) have been used for microgels synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…It has recently been shown that the photo‐isomerization rate of the surfactant in bulk and at the interface (such as surfaces, polymers, aggregates) differs. [ 47,48 ] Here we expand the analysis of Δ c C to give an estimation of the fluid flow direction and strength for the l ‐LDDO velocity by considering the change in the excess of concentration with the irradiation time as a consequence of isomerization rate, which was especially important for the first few seconds of irradiation till the photo‐stationary state was achieved: dΔcnormalCdt=dcC,PdtdcC,Bdt where d c C,P /dt and d c C,B /dt are time‐dependent changes in the cis ‐isomer concentrations at the particle interface and in bulk solution. Inserting rate equations of isomerization at interface, d c C,P /d t , and bulk, d c C,B /d t , [50] one gets: dcC,Pdt=kTC,I ·I· cT,P=kTC,I ·I·Aeff·θnormalTcnormalT,normalB and d c C,B /dt: dcC,Bdt=kTC ·I·cT,BkCT·I·cC,B and finally: dΔnormalcnormalCdt I· []kTC,I·Aeff·θT...…”
Section: Methodsmentioning
confidence: 99%
“…It has recently been shown that the photo-isomerization rate of the surfactant in bulk and at the interface (such as surfaces, polymers, aggregates) differs. [47,48] Here we expand the analysis of Δc C to give an estimation of the fluid flow direction and strength for the l-LDDO velocity by considering the change in the excess of concentration with the irradiation time as a consequence of isomerization rate, which was especially important for the first few seconds of irradiation till the photo-stationary state was achieved:…”
Section: Theoretical Backgroundmentioning
confidence: 99%